Exploring the challenges faced by a novice administrator: A case study - Mithat Ekinci; Yasemin Kırkgöz (Universitas Ahmad Dahlan, 2023)
With the changing world and the developing technology, many alterations occur throughout the world as a whole. Managing and directing an educational institution is not an exception. The teaching and learning process, as well as the place of stakeholders of these educational institutions, are currently in a period of development as the governments are concerned with raising the standards of education. All these changes and standardization movements put pressure on the administrators, especially on those new to such positions. The situation becomes even worse when these administrators lack the necessary experience and training. To draw attention to these issues, this case study aimed to elicit the opinions of a novice administrator concerning leadership and administration practices and identify the critical challenges she faced during the first year of her appointment. A qualitative case study research methodology was employed in the present research. Two different data collection tools were used: a semi-structured interview with the participant administrator and a diary of the participant. Content analysis was used to analyze the obtained data. The results of the study demonstrated that working as a novice administrator is a gratifying task, yet, it creates personal, occupational and relational challenges for the administrator.